2013
DOI: 10.2522/ptj.20120190
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Addition of Modified Pilates Exercises to a Minimal Intervention in Patients With Chronic Low Back Pain: A Randomized Controlled Trial

Abstract: Background The Pilates method has been used to improve function and reduce pain in patients with chronic nonspecific low back pain, although there is little scientific evidence that describes its efficacy. Objective The purpose of this study was to investigate the effectiveness of the addition of modified Pilates exercises to minimal intervention in patients with chronic low back pain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
119
2
22

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(147 citation statements)
references
References 37 publications
4
119
2
22
Order By: Relevance
“…The improvements on the PSFS in our participants were similar to those experienced in other randomized clinical trials [45][46][47][48] ; however, our participants reported higher PSFS scores 1 month post-treatment. In a study examining the effects of motor control exercises on LBP, Aasa et al 49 reported a mean PSFS baseline score of 3.8 and a 2-month follow-up score of 7.8.…”
Section: Discussionsupporting
confidence: 87%
“…The improvements on the PSFS in our participants were similar to those experienced in other randomized clinical trials [45][46][47][48] ; however, our participants reported higher PSFS scores 1 month post-treatment. In a study examining the effects of motor control exercises on LBP, Aasa et al 49 reported a mean PSFS baseline score of 3.8 and a 2-month follow-up score of 7.8.…”
Section: Discussionsupporting
confidence: 87%
“…The level was set according to the physical condition of each participant 23 . Some basic exercises were adapted to the conditions of the participant.…”
Section: Interventionsmentioning
confidence: 99%
“…Ainda assim, o conhecimento sobre dor de cabeça e atividade física é limitado e poucos estudos tem avaliado este relacionamento. 29 Contudo, a maioria dos estudos não encontrou redução significativa da frequência ou duração das crises de cefaléia, 30 mas sugere que o exercício ativa sinais de neurotransmissor endógeno, que poderiam ser eficazes na redução da intensidade da dor da enxaqueca. 31 O resultado positivo para a paciente com a patologia enxaqueca foi notável nesta pesquisa, corroborando com os estudos acerca dos benefícios da atividade física nestes casos.…”
Section: Discussionunclassified